A pressure-resistant and moisture-resistant packaging carton for shower sanitary wares and a method for manufacturing the same
Patent Information
- Application Number
- CN202611103538.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,现有的淋浴卫具包装纸箱综合性能仍存在以下缺陷:多数纸箱在潮湿环境下易发生纤维吸湿软化,导致结构强度大幅下降,无法承受多层堆叠压力而变形破损,影响淋浴卫具运输安全性;此外,部分纸箱防潮组分与基材的结合稳定性欠佳,在长期存储或复杂环境下防潮效果衰减较快,难以保障纸箱长期使用的结构完整性,亦无法满足淋浴卫具对包装的长效防护需求
漂白硫酸盐针叶木浆与竹浆纤维构成包装纸箱的主体基材,为纸箱提供基础结构强度与纤维交织性能;丙烯酸酯共聚乳液可在纤维表面形成致密膜层,与疏水气相法二氧化硅协同作用,显著提升纸箱整体防潮性能;芳纶浆粕可增强纸箱的抗破损性与抗压性,介孔二氧化硅负载木质素磷酸酯复合物能优化纤维间的界面结合性能,提升纸箱的环境适应性与结构稳定性;羟丙基甲基纤维素醚可为组分间提供初始粘结力,并辅助封闭纤维孔隙;聚多巴胺改性海泡石纤维可显著改善各组分间的界面相容性,促进应力在基材内部的高效传递;封闭型水性异氰酸酯交联剂能形成化学交联网络,提升各组分间的结合稳定性;防霉剂可抑制霉菌滋生,保障纸箱存储过程中的结构完整性;阳离子聚丙烯酰胺有助于提升疏水气相法二氧化硅在浆料中的留着率,确保防潮组分充分发挥作用;各组分协同作用、互补增效,使该包装纸箱具备优异的结构强度、防潮性、防霉性、抗压性与抗破损性等综合性能,可有效延长其使用寿命,满足淋浴卫具仓储与运输的防护需求。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of packaging carton technology, specifically to a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware and its preparation method. Background Technology
[0002] During storage and transportation, the packaging cartons for shower fixtures must withstand both stacking pressure and the effects of humid environments. Existing packaging cartons are mostly made from plant fibers as the base material, combined with conventional moisture-proof and reinforcing components to meet basic packaging protection needs. These cartons form a stable structural framework through fiber interweaving, providing basic structural strength. After simple moisture-proofing treatment, they resist environmental moisture and are widely used in the packaging of various items.
[0003] However, the existing packaging cartons for shower and bathroom fixtures still have the following defects in overall performance: most cartons are prone to fiber softening due to moisture absorption in humid environments, resulting in a significant decrease in structural strength. They cannot withstand the pressure of multiple stacks and are deformed and damaged, affecting the safety of shower and bathroom fixture transportation. In addition, the bonding stability between the moisture-proof components of some cartons and the substrate is not good. The moisture-proof effect decays quickly in long-term storage or complex environments, making it difficult to ensure the structural integrity of the cartons for long-term use and failing to meet the long-term protection requirements of shower and bathroom fixture packaging. Summary of the Invention
[0004] To address the problems existing in the prior art, the present invention provides a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware and its preparation method.
[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention discloses a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware. By weight, the raw materials for its preparation include: 40-70 parts of bleached sulfate softwood pulp, 10-25 parts of bamboo pulp fiber, 15-30 parts of acrylate copolymer emulsion, 2-6 parts of hydrophobic fumed silica, 3-10 parts of aramid pulp, 2-6 parts of mesoporous silica-supported lignin phosphate complex, 5-15 parts of hydroxypropyl methylcellulose ether, 1-4 parts of polydopamine-modified sepiolite fiber, 2-4 parts of blocked waterborne isocyanate crosslinking agent, 0.5-1.1 parts of mildew inhibitor, and 0.2-0.5 parts of cationic polyacrylamide.
[0006] Using the above technical solution, bleached sulfate softwood pulp and bamboo pulp fiber constitute the main substrate of the packaging carton, providing the carton with basic structural strength and fiber interweaving performance; acrylate copolymer emulsion can form a dense film layer on the fiber surface, which, in synergy with hydrophobic fumed silica, significantly improves the overall moisture-proof performance of the carton; aramid pulp can enhance the carton's resistance to breakage and compression; mesoporous silica-loaded lignin phosphate composite can optimize the interfacial bonding performance between fibers, improving the carton's environmental adaptability and structural stability; hydroxypropyl methylcellulose ether can provide initial bonding force between components and assist in sealing fiber pores; polydopamine-modified sepiolite fiber can... Significantly improves the interfacial compatibility between components and promotes efficient stress transfer within the substrate; the closed-type waterborne isocyanate crosslinking agent can form a chemical crosslinking network, enhancing the bonding stability between components; the mildew inhibitor can inhibit mold growth and ensure the structural integrity of the carton during storage; cationic polyacrylamide helps improve the retention rate of hydrophobic fumed silica in the slurry, ensuring that the moisture-proof components play a full role; the synergistic effect and complementary synergistic effect of each component give the packaging carton excellent comprehensive performance in terms of structural strength, moisture resistance, mildew resistance, compression resistance and damage resistance, which can effectively extend its service life and meet the protection needs of shower and sanitary ware storage and transportation.
[0007] Preferably, the bleached sulfate softwood pulp has a freeness of 32-38°SR, and the bamboo pulp fiber has a freeness of 20-28°SR; the acrylate copolymer emulsion has a solid content of 40%-45%; and the mildew inhibitor is zinc pyrithione or isothiazolinone.
[0008] Using the above technical solutions, the beating degree of bleached sulfate softwood pulp is controlled at 32-38°SR, which ensures that the fibers have suitable interlacing ability and paper structure strength; the beating degree of bamboo pulp fiber is set at 20-28°SR, which can maintain the toughness of the fiber itself and form a structurally stable substrate network with bleached sulfate softwood pulp; the solid content of acrylic copolymer emulsion is maintained at 40%-45%, which can form a continuous and uniform film layer on the fiber surface and improve the moisture-proof performance of the carton; the anti-mold agent is selected from zinc pyrithione or isothiazolinone, which can inhibit the growth of mold on the surface and inside of the carton and maintain the structural integrity and performance stability of the carton during storage.
[0009] Preferably, the raw materials for preparing the mesoporous silica-supported lignin phosphate complex, by weight, include: 80-120 parts of alkali lignin, 15-30 parts of phosphorus pentoxide, 2-5 parts of hexadecyltrimethylammonium bromide, 20-30 parts of tetraethyl orthosilicate, 5-10 parts of ammonia, 350-450 parts of N,N-dimethylformamide, 150-230 parts of anhydrous ethanol, and 300-500 parts of deionized water.
[0010] Using the above technical solution, alkali lignin serves as the core substrate, providing skeletal support and reactive sites for the mesoporous silica-supported lignin phosphate complex. Phosphorus pentoxide, dissolved in N,N-dimethylformamide, forms an acidic system that undergoes esterification with the hydroxyl groups of alkali lignin to form a lignin phosphate structure, enhancing the complex's strengthening and moisture-proof potential. Hexadecyltrimethylammonium bromide forms a micelle template in the reaction system, providing a foundation for the construction of an ordered mesoporous structure. Tetraethyl orthosilicate, as a silicon source, hydrolyzes and condenses to form a silica shell, achieving the coating of lignin phosphate. Ammonia is used to adjust the pH of the reaction system, promoting the hydrolysis of tetraethyl orthosilicate and stabilizing the micelle template. N,N-dimethylformamide, as a reaction solvent, dissolves alkali lignin and phosphorus pentoxide, ensuring the reaction proceeds fully. Anhydrous ethanol and deionized water are used to disperse the reaction components and wash the products, improving the purity and structural stability of the complex.
[0011] Preferably, the preparation method of the mesoporous silica-supported lignin phosphate complex includes the following steps: 1) In a dry reaction vessel, add alkali lignin and N,N-dimethylformamide in a mixture of 2 / 3-5 / 6 of their total mass, and stir at 200-400 r / min for 30-60 min to dissolve. 2) Dissolve phosphorus pentoxide in the remaining N,N-dimethylformamide at 42-46℃; heat the system obtained in step 1) to 70-85℃, purge with nitrogen at a rate of 0.2-0.5 L / min for protection throughout the process, and add the mixture of phosphorus pentoxide and N,N-dimethylformamide dropwise at a rate of 5-10 mL / min while stirring continuously at 200-400 r / min. After the addition is complete, continue stirring and react for 3-5 h. 3) After the reaction is complete, pour the reaction solution obtained in step 2) into ice water at 0-5℃. The volume of ice water is 3-5 times the volume of the reaction solution. Let it stand for 30-60 minutes to settle, and then perform vacuum filtration. The filter paper pore size is 0.45-1.0μm, and the filtration pressure is -0.06MPa to -0.08MPa. 4) The solid obtained by vacuum filtration is washed with deionized water 3-5 times, and the mass of deionized water used each time is 10-15 times the mass of the solid. The washing is continued until the pH of the filtrate is 6.5-7.5. Then the washed solid is placed in a vacuum drying oven at 60-80℃ and a vacuum degree of -0.08MPa to -0.09MPa and dried for 10-16 hours to obtain phosphate ester grafted modified lignin. 5) Disperse phosphate-grafted lignin and hexadecyltrimethylammonium bromide in a mixed solvent of all deionized water and anhydrous ethanol, and ultrasonically disperse for 30-60 min at an ultrasonic frequency of 20-40 kHz and a power of 300-500 W; then adjust the pH of the system to 11.5-12.0 with ammonia water with a mass fraction of 25%-28%, raise the temperature to 50-55℃, and pre-assemble at a stirring speed of 300-500 r / min for 2-3 h. 6) Add tetraethyl orthosilicate in three equal volumes to the system obtained in step 5), with an interval of 2-3 hours between each batch, at a dropping rate of 10-15 mL / min. After the addition is complete, perform hydrothermal treatment at 80-85℃ for 12-16 hours. After the reaction is complete, centrifuge at 3000-5000 r / min for 10-15 minutes and collect the solid product. Wash the solid product with deionized water and anhydrous ethanol 3-4 times each, with each washing liquid volume being 8-10 times the mass of the solid. After Soxhlet extraction with anhydrous ethanol for 12-16 hours to remove residual hexadecyltrimethylammonium bromide, dry it at 55-65℃ and a vacuum of -0.08 MPa to -0.09 MPa for 10-16 hours to obtain the mesoporous silica-supported lignin phosphate complex.
[0012] Using the above technical solution, the stepwise addition of N,N-dimethylformamide and controlled stirring conditions can fully dissolve alkali lignin, providing a homogeneous system for subsequent reactions. Nitrogen protection throughout the process maintains the stability of the reaction environment, ensuring the full grafting reaction between phosphorus pentoxide and alkali lignin, generating structurally stable phosphate-grafted modified lignin. Ice-water precipitation and vacuum filtration, combined with specific filter paper pore size and pressure, effectively separate products from impurities. Deionized water washing and vacuum drying adjust the product pH to neutral and remove moisture, improving the purity of the phosphate-grafted modified lignin. Ultrasonic dispersion ensures uniform dispersion of the phosphate-grafted modified lignin and hexadecyltrimethylammonium bromide. Ammonia water pH adjustment and pre-assembly steps provide conditions for the formation of an ordered mesoporous structure. Batch-wise dropwise addition of tetraethyl orthosilicate combined with hydrothermal treatment achieves uniform coating of lignin phosphate with silica. Centrifugation, washing, and Soxhlet extraction remove residual impurities. Finally, drying yields a structurally regular mesoporous silica-supported lignin phosphate complex with both reinforcing and moisture-proof potential.
[0013] Preferably, the raw materials for preparing the polydopamine-modified sepiolite fiber, by weight, include: 15-25 parts sepiolite fiber, 3-6 parts dopamine hydrochloride, 5-10 parts 3-aminopropyltriethoxysilane, 0.5-1.0 parts ammonium persulfate, 150-250 parts Tris-HCl buffer solution with a concentration of 0.01-0.02 mol / L, 0.1-0.3 parts sodium sulfite, and 200-300 parts deionized water.
[0014] Using the above technical solution, sepiolite fiber serves as the base component, providing structural support and reinforcement for polydopamine-modified sepiolite fiber; dopamine hydrochloride can polymerize during the reaction to form a polydopamine layer, enhancing the bonding ability of the fiber with other components; 3-aminopropyltriethoxysilane can modify the sepiolite fiber, introducing active groups to promote the grafting and adhesion of the polydopamine layer; ammonium persulfate, as an oxidant, can initiate the polymerization reaction of dopamine hydrochloride, ensuring the smooth progress of the reaction; a Tris-HCl buffer solution with a concentration of 0.01-0.02 mol / L maintains the pH stability of the reaction system, providing a suitable environment for the polymerization reaction; sodium sulfite, as a bleaching inhibitor, can improve the appearance and color of the product and control the brightness index of the product; deionized water is used to disperse the raw material components and wash the reaction products, improving the purity and structural stability of the final product.
[0015] Preferably, the preparation method of the polydopamine-modified sepiolite fiber includes the following steps: (1) Disperse sepiolite fibers in all deionized water, stir at 300-500 r / min for 30-60 min, adjust the pH of the system to 9.0-9.5 with ammonia water with a mass fraction of 25%-28%, add 3-aminopropyltriethoxysilane, heat to 60-65℃, and stir at 300-500 r / min for 4-6 h. (2) After the reaction is complete, the pH of the system obtained in step (1) is neutralized to 6.5-7.0 with 0.1-0.2 mol / L dilute hydrochloric acid. After filtration, it is washed 3-4 times with deionized water and dried at 75-85℃ for 10-14h to obtain cationic modified sepiolite. (3) Disperse the cationic modified sepiolite in Tris-HCl buffer, and ultrasonically disperse it for 30-60 min under ultrasonic frequency of 20-40 kHz and power of 300-500 W. Add dopamine hydrochloride and ammonium persulfate, and polymerize it at 200-300 r / min for 6-8 h under light-protected conditions at 25-30 ℃. (4) After the reaction is completed, centrifuge at 3000-5000 r / min for 10-15 min, collect the solid, disperse the obtained solid in deionized water at a solid-liquid mass ratio of 1:8-10, add sodium sulfite, adjust the pH to 4.5-5.5 with 0.05 mol / L dilute hydrochloric acid, stir at 200-300 r / min for 20-30 min under nitrogen protection, then centrifuge again, collect the solid and wash it with deionized water 2-3 times, and then dry it at 55-65℃ and vacuum degree of -0.08MPa to -0.09MPa for 10-14 h to obtain polydopamine modified sepiolite fiber.
[0016] By employing the above technical solution, adjusting the pH of the system to a specific range and controlling the reaction temperature, the grafting reaction between 3-aminopropyltriethoxysilane and sepiolite fibers can be promoted. The neutralization, washing, and drying steps can remove impurities, resulting in structurally stable cationic modified sepiolite. Ultrasonic dispersion ensures that the cationic modified sepiolite is uniformly dispersed in Tris-HCl buffer solution. The light-protected environment provides suitable conditions for the polymerization reaction of dopamine hydrochloride and ammonium persulfate, forming a polydopamine layer that adheres to the surface of the sepiolite fibers. The addition of sodium sulfite under nitrogen protection to adjust the pH ensures the color and purity of the product. Further centrifugation, washing, and vacuum drying further remove residual impurities, ultimately yielding polydopamine-modified sepiolite fibers that possess both reinforcing properties and interfacial bonding capabilities.
[0017] This invention also discloses a method for preparing a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware, comprising the following steps: S1. Slurry preparation: Bleached sulfate softwood pulp, bamboo pulp fiber, aramid pulp, mesoporous silica-supported lignin phosphate complex, and polydopamine-modified sepiolite fiber are added to a hydrapulper for pulping, then transferred to a desizing machine. Deionized water is added until the total mass fraction of the pulp is 4.0%-6.0%. Cationic polyacrylamide is added, and the pulp is desizing at 40-50℃ for 30-40 minutes to obtain primary pulp. S2, Functional slurry mixing: Add 1 / 2 to 2 / 3 of the total mass of the acrylate copolymer emulsion, 7 / 10 to 4 / 5 of the total mass of the hydrophobic fumed silica, the blocked waterborne isocyanate crosslinking agent, the mildew inhibitor, and the hydroxypropyl methylcellulose ether to a mixing container and premix evenly. Then add it to the primary slurry obtained in step S1 and stir at 300-500 r / min for 10-20 min. Adjust the pH of the slurry to 6.5-7.5 with 0.05-0.1 mol / L dilute ammonia or dilute hydrochloric acid to obtain the functional composite slurry. S3. Paper web forming and dewatering: The functional composite pulp is diluted to a head concentration of 0.8%-1.2% and then fed to the wire section of the fourdrinier paper machine. After vacuum filtration at a vacuum degree of -0.03MPa to -0.05MPa and three-stage press dewatering, a wet paper web is obtained. S4. Drying and Surface Treatment: The wet paper web is subjected to gradient drying to a moisture content of 6%-8%, followed by the application of a reinforced moisture-proof coating on its surface using a roller coating method. The coating material is composed of a uniform mixture of the remaining acrylic copolymer emulsion and the remaining hydrophobic fumed silica, with a coating weight of 8-15 g / m². 2 The solid content of the coating is 15%-20%; S5. Pressing and Corrugating: The paper web obtained in step S4 is passed through a single-face corrugator and processed under conditions of temperature 150-165℃, pressure 0.3-0.5MPa, and paperboard speed 60-90m / min to produce AB type corrugated paperboard (A flute height 4.5-5.0mm, number of flutes 34-38 / 300mm; B flute height 2.5-3.0mm, number of flutes 48-52 / 300mm). S6. Die-cutting and gluing: Based on the size and shape of the shower fixtures, the corrugated cardboard is sequentially die-cut, printed, and grooved, and then bonded into boxes using polyurethane adhesive.
[0018] Using the above technical solutions, the decomposition process at a specific temperature ensures uniform dispersion of the reinforcing and base material components, while cationic polyacrylamide improves component retention, laying a stable structural foundation for the paperboard. Functional components are pre-mixed and then stirred with the primary pulp, adjusting the pH to a suitable range to ensure synergistic effects and enhance the paperboard's bonding and moisture-proof capabilities. Vacuum filtration molding and three-stage pressing dewatering improve the density of the wet paper web, reducing residual moisture. Gradient drying controls the paperboard's moisture content, and a reinforced moisture-proof coating further blocks water vapor penetration. AB-type corrugated paperboard, formed under specific parameters, possesses both good cushioning and compression resistance, meeting the protective needs of shower and bathroom fixtures. After die-cutting, printing, and slotting, polyurethane adhesive bonding ensures neat carton formation, with sealing and structural strength meeting transportation and storage requirements.
[0019] Preferably, in step S1, the speed of the hydraulic pulper is 300-500 r / min; in step S2, the stirring speed of the premix is 300-500 r / min, and the time is 10-15 min.
[0020] By adopting the above technical solution, the specific rotation speed of the hydraulic pulper can fully dissociate and initially mix the substrates such as bleached sulfate softwood pulp and bamboo pulp fiber with other components, avoiding excessive fiber damage and ensuring the uniformity and structural stability of the primary pulp. The fixed stirring speed and time in the premixing stage can allow functional components such as acrylic copolymer emulsion and hydrophobic fumed silica to quickly fuse and form a uniformly dispersed mixed system, laying the foundation for efficient bonding with the primary pulp in the future, reducing component agglomeration and improving the synergistic effect between various substances.
[0021] Preferably, in step S3, the dewatering pressures of the three presses are 0.2-0.3 MPa, 0.3-0.4 MPa, and 0.4-0.5 MPa respectively, and the paper web running speed is 8-12 m / min; the dryness of the wet paper web after pressing is 18%-22%.
[0022] By adopting the above technical solution, the progressively increasing pressure of the three presses, combined with an appropriate paper web running speed, can gradually remove moisture from the functional composite pulp, avoiding problems such as damage and wrinkling of the wet paper web due to sudden pressure changes, and ensuring the integrity of the paper web structure. After pressing, controlling the dryness of the wet paper web within a specific range not only lays the foundation for subsequent gradient drying processes, reducing drying energy consumption and time, but also allows the fibers to initially adhere to the various functional components, improving the density and bonding stability of the paperboard after forming, and providing support for the subsequent enhancement of moisture resistance and compression resistance.
[0023] Preferably, in step S4, the gradient drying is as follows: the first zone is 80-95℃, drying for 30-40s; the second zone is 100-110℃, drying for 35-45s; the third zone is 115-125℃, drying for 25-35s; and the paper web running speed during the drying process is 10-15m / min.
[0024] By employing the above technical solution, the gradually increasing drying temperature, combined with appropriate drying time and paper web running speed, can gradually remove moisture from the wet paper web, avoiding uneven shrinkage, cracking, or separation of fibers from functional components due to excessively rapid heating, thus ensuring the integrity of the paperboard forming. The matching settings of drying parameters in each area can ensure that the moisture content of the paperboard is uniformly reduced to the target range, promoting the formation of a dense hydrophobic film layer in the acrylic copolymer emulsion, strengthening the adhesion between fibers and components, and improving the density of the paperboard structure, thus providing a guarantee for subsequent moisture-proof and compression-resistant performance.
[0025] The beneficial effects of this invention are as follows: Bleached sulfate softwood pulp and bamboo pulp fiber constitute the main substrate of packaging cartons, providing basic structural strength and fiber interweaving properties. Acrylic ester copolymer emulsion can form a dense film layer on the fiber surface, synergistically improving the overall moisture resistance of the cartons in conjunction with hydrophobic fumed silica. Aramid pulp enhances the cartons' resistance to breakage and compression, while mesoporous silica-loaded lignin phosphate complex optimizes interfacial bonding between fibers, improving the environmental adaptability and structural stability of the cartons. Hydroxypropyl methylcellulose ether provides initial adhesion between components and helps seal fiber pores. Polydopamine-modified sepiolite fibers significantly improve various properties. The interfacial compatibility between components promotes efficient stress transfer within the substrate; the closed-type waterborne isocyanate crosslinking agent forms a chemical crosslinking network, enhancing the bonding stability between components; the mildew inhibitor inhibits mold growth, ensuring the structural integrity of the carton during storage; cationic polyacrylamide helps improve the retention rate of hydrophobic fumed silica in the slurry, ensuring the moisture-proof components function fully; the synergistic and complementary effects of the components give the packaging carton excellent comprehensive performance in terms of structural strength, moisture resistance, mildew resistance, compression resistance, and breakage resistance, effectively extending its service life and meeting the protection requirements for the storage and transportation of shower and sanitary ware. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] The specific information on the raw materials used in the embodiments of the present invention is shown in Table 1.
[0028] Table 1
[0029] Example 1 discloses a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware. By weight, the raw materials for its preparation include: 40 parts of bleached sulfate softwood pulp with a beating degree of 32°SR, 10 parts of bamboo pulp fiber with a beating degree of 20°SR, 15 parts of acrylic copolymer emulsion with a solid content of 40%, 2 parts of hydrophobic fumed silica, 3 parts of aramid pulp, 2 parts of mesoporous silica-supported lignin phosphate composite, 5 parts of hydroxypropyl methylcellulose ether, 1 part of polydopamine-modified sepiolite fiber, 2 parts of blocked waterborne isocyanate crosslinking agent, 0.5 parts of zinc pyrithione, and 0.2 parts of cationic polyacrylamide.
[0030] The raw materials for preparing the mesoporous silica-supported lignin phosphate complex, by weight, include: 80 parts alkali lignin, 15 parts phosphorus pentoxide, 2 parts hexadecyltrimethylammonium bromide, 20 parts tetraethyl orthosilicate, 5 parts ammonia, 350 parts N,N-dimethylformamide, 150 parts anhydrous ethanol, and 300 parts deionized water.
[0031] The preparation method of mesoporous silica-supported lignin phosphate complex includes the following steps: 1) In a dry reaction vessel, add alkali lignin and 2 / 3 of the total mass of N,N-dimethylformamide, and stir at 200 r / min for 30 min to dissolve; 2) Dissolve phosphorus pentoxide in the remaining N,N-dimethylformamide at 42℃; heat the system obtained in step 1) to 70℃, purge with nitrogen at a rate of 0.2 L / min for protection throughout the process, and add the mixture of phosphorus pentoxide and N,N-dimethylformamide dropwise at a rate of 5 mL / min while stirring continuously at 200 r / min. After the addition is complete, continue stirring and react for 3 h. 3) After the reaction is complete, pour the reaction solution obtained in step 2) into ice water at 0°C. The volume of ice water is 3 times the volume of the reaction solution. Let it stand for 30 minutes to settle, and then perform vacuum filtration. The filter paper pore size is 0.45μm and the filtration pressure is -0.06MPa. 4) The solid obtained by vacuum filtration was washed three times with deionized water. The mass of deionized water used each time was 10 times the mass of the solid. The washing continued until the pH of the filtrate was 6.5. Then the washed solid was placed in a vacuum drying oven at 60℃ and a vacuum degree of -0.08MPa and dried for 10 hours to obtain phosphate ester grafted modified lignin. 5) Phosphate-grafted modified lignin and hexadecyltrimethylammonium bromide were dispersed in a mixed solvent of all deionized water and anhydrous ethanol and ultrasonically dispersed for 30 min at an ultrasonic frequency of 20 kHz and a power of 300 W. Then, the pH of the system was adjusted to 11.5 with 25% ammonia water, the temperature was raised to 50 °C, and pre-assembled at a stirring speed of 300 r / min for 2 h. 6) Add tetraethyl orthosilicate in three equal volumes to the system obtained in step 5), with an interval of 2 hours between each batch, at a dropping rate of 10 mL / min. After the addition is complete, perform hydrothermal treatment at 80 °C for 12 hours. After the reaction is complete, centrifuge at 3000 r / min for 10 minutes and collect the solid product. Wash the solid product three times each with deionized water and anhydrous ethanol, with each washing liquid volume being 8 times the mass of the solid. After Soxhlet extraction with anhydrous ethanol for 12 hours to remove residual hexadecyltrimethylammonium bromide, dry at 55 °C and vacuum degree -0.08 MPa for 10 hours to obtain the mesoporous silica-supported lignin phosphate complex.
[0032] The raw materials for preparing polydopamine-modified sepiolite fiber, by weight, include: 15 parts sepiolite fiber, 3 parts dopamine hydrochloride, 5 parts 3-aminopropyltriethoxysilane, 0.5 parts ammonium persulfate, 150 parts Tris-HCl buffer solution with a concentration of 0.01 mol / L, 0.1 parts sodium sulfite, and 200 parts deionized water.
[0033] The preparation method of polydopamine-modified sepiolite fiber includes the following steps: (1) Disperse sepiolite fibers in all deionized water, stir at 300 r / min for 30 min, adjust the pH of the system to 9.0 with 25% ammonia water, add 3-aminopropyltriethoxysilane, heat to 60℃, and stir at 300 r / min for 4 h. (2) After the reaction is complete, the pH of the system obtained in step (1) is neutralized to 6.5 with 0.1 mol / L dilute hydrochloric acid, filtered and washed 3 times with deionized water, and dried at 75°C for 10 h to obtain cationic modified sepiolite. (3) The cationic modified sepiolite was dispersed in Tris-HCl buffer and ultrasonically dispersed for 30 min at an ultrasonic frequency of 20 kHz and a power of 300 W. Dopamine hydrochloride and ammonium persulfate were added and polymerized at 200 r / min for 6 h under the dark at 25 °C. (4) After the reaction was completed, the solid was collected by centrifugation at 3000 r / min for 10 min. The solid was dispersed in deionized water at a solid-liquid mass ratio of 1:8. Sodium sulfite was added, and the pH was adjusted to 4.5 with 0.05 mol / L dilute hydrochloric acid. The mixture was stirred at 200 r / min for 20 min under nitrogen protection. Then, the solid was collected by centrifugation again and washed twice with deionized water. The solid was then dried at 55℃ and vacuum degree -0.08 MPa for 10 h to obtain polydopamine modified sepiolite fiber.
[0034] This embodiment also discloses a method for preparing a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware, comprising the following steps: S1. Slurry preparation: Bleached sulfate softwood pulp, bamboo pulp fiber, aramid pulp, mesoporous silica-supported lignin phosphate complex, and polydopamine-modified sepiolite fiber were added to a hydrapulper at a speed of 300 r / min. After pulping, the pulp was transferred to a desizing machine, and deionized water was added until the total mass fraction of the pulp was 4.0%. Cationic polyacrylamide was added, and the pulp was desizing at 40°C for 30 min to obtain primary pulp. S2, Functional slurry mixing: Half of the total mass of the acrylate copolymer emulsion, 7 / 10 of the total mass of the hydrophobic fumed silica, the blocked waterborne isocyanate crosslinking agent, zinc pyridine thione, and hydroxypropyl methylcellulose ether were added to a mixing container and premixed at 300 r / min for 10 min. Then, the mixture was added to the primary slurry obtained in step S1 and stirred at 300 r / min for 10 min. The pH of the slurry was adjusted to 6.5 with 0.05 mol / L dilute ammonia or dilute hydrochloric acid to obtain the functional composite slurry. S3. Paper web forming and dewatering: After diluting the functional composite pulp to a head concentration of 0.8%, it is fed to the wire section of the fourdrinier paper machine. After vacuum filtration at a vacuum degree of -0.03MPa and three-stage press dewatering, a wet paper web with a dryness of 18% is obtained. The dewatering pressures of the three presses are 0.2 MPa, 0.3 MPa, and 0.4 MPa, respectively, and the paper web running speed is 8 m / min. S4. Drying and Surface Treatment: The wet paper web is subjected to gradient drying to a moisture content of 6%, followed by the application of a reinforced moisture-proof coating on its surface using a roller coating method. The coating material is composed of a uniform mixture of the remaining acrylic copolymer emulsion and the remaining hydrophobic fumed silica, with a coating weight of 8 g / m². 2 The solid content of the coating is 15%. The gradient drying process is as follows: Zone 1, 80℃, drying for 30 seconds; Zone 2, 100℃, drying for 35 seconds; Zone 3, 115℃, drying for 25 seconds; the paper web running speed during the drying process is 10 m / min. S5. Pressing and Corrugating: The paper web obtained in step S4 is passed through a single-face corrugator and made into AB type corrugated board (A flute height 4.5mm, number of flutes 34 / 300mm; B flute height 2.5mm, number of flutes 48 / 300mm) under the conditions of temperature 150℃, pressure 0.3MPa and board speed 60m / min. S6. Die-cutting and gluing: Based on the size and shape of the shower fixtures, the corrugated cardboard is sequentially die-cut, printed, and grooved, and then bonded into boxes using polyurethane adhesive.
[0035] Example 2 discloses a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware. By weight, the raw materials for its preparation include: 70 parts of bleached sulfate softwood pulp with a beating degree of 38°SR, 25 parts of bamboo pulp fiber with a beating degree of 28°SR, 30 parts of acrylic copolymer emulsion with a solid content of 45%, 6 parts of hydrophobic fumed silica, 10 parts of aramid pulp, 6 parts of mesoporous silica-supported lignin phosphate composite, 15 parts of hydroxypropyl methylcellulose ether, 4 parts of polydopamine-modified sepiolite fiber, 4 parts of blocked waterborne isocyanate crosslinking agent, 1.1 parts of isothiazolinone, and 0.5 parts of cationic polyacrylamide.
[0036] The raw materials for preparing the mesoporous silica-supported lignin phosphate complex, by weight, include: 120 parts alkali lignin, 30 parts phosphorus pentoxide, 5 parts hexadecyltrimethylammonium bromide, 30 parts tetraethyl orthosilicate, 10 parts ammonia, 450 parts N,N-dimethylformamide, 230 parts anhydrous ethanol, and 500 parts deionized water.
[0037] The preparation method of mesoporous silica-supported lignin phosphate complex includes the following steps: 1) In a dry reaction vessel, add alkali lignin and 5 / 6 of the total mass of N,N-dimethylformamide, and stir at 400 r / min for 60 min to dissolve; 2) Dissolve phosphorus pentoxide in the remaining N,N-dimethylformamide at 46℃; heat the system obtained in step 1) to 85℃, purge with nitrogen at a rate of 0.5 L / min for protection throughout the process, and add the mixture of phosphorus pentoxide and N,N-dimethylformamide dropwise at a rate of 10 mL / min while stirring continuously at 400 r / min. After the addition is complete, continue stirring and react for 5 h. 3) After the reaction is complete, pour the reaction solution obtained in step 2) into ice water at 5°C. The volume of ice water is 5 times the volume of the reaction solution. Let it stand and precipitate for 60 minutes, and then perform vacuum filtration. The filter paper pore size is 1.0 μm and the filtration pressure is -0.08 MPa. 4) The solid obtained by vacuum filtration was washed 5 times with deionized water. The mass of deionized water used each time was 15 times the mass of the solid. The washing continued until the pH of the filtrate was 7.5. Then the washed solid was placed in a vacuum drying oven at 80℃ and a vacuum degree of -0.09MPa and dried for 16 hours to obtain phosphate ester grafted modified lignin. 5) Phosphate-grafted modified lignin and hexadecyltrimethylammonium bromide were dispersed in a mixed solvent of all deionized water and anhydrous ethanol and ultrasonically dispersed for 60 min at an ultrasonic frequency of 40 kHz and a power of 500 W. Then, the pH of the system was adjusted to 12.0 with 28% ammonia water, the temperature was raised to 55 °C, and pre-assembled for 3 h with a stirring speed of 500 r / min. 6) Add tetraethyl orthosilicate in three equal volumes to the system obtained in step 5), with an interval of 3 hours between each batch, at a dropping rate of 15 mL / min. After the addition is complete, perform hydrothermal treatment at 85 °C for 16 hours. After the reaction is complete, centrifuge at 5000 r / min for 15 minutes and collect the solid product. Wash the solid product four times each with deionized water and anhydrous ethanol, with each washing liquid volume being 10 times the mass of the solid. After Soxhlet extraction with anhydrous ethanol for 16 hours to remove residual hexadecyltrimethylammonium bromide, dry at 65 °C and vacuum degree -0.09 MPa for 16 hours to obtain the mesoporous silica-supported lignin phosphate complex.
[0038] The raw materials for preparing polydopamine-modified sepiolite fiber, by weight, include: 25 parts sepiolite fiber, 6 parts dopamine hydrochloride, 10 parts 3-aminopropyltriethoxysilane, 1 part ammonium persulfate, 250 parts Tris-HCl buffer solution with a concentration of 0.02 mol / L, 0.3 parts sodium sulfite, and 300 parts deionized water.
[0039] The preparation method of polydopamine-modified sepiolite fiber includes the following steps: (1) Disperse sepiolite fibers in all deionized water, stir at 500 r / min for 60 min, adjust the pH of the system to 9.5 with 28% ammonia water, add 3-aminopropyltriethoxysilane, heat to 65℃, and stir at 500 r / min for 6 h. (2) After the reaction was completed, the pH of the system obtained in step (1) was neutralized to 7.0 with 0.2 mol / L dilute hydrochloric acid, filtered and washed 4 times with deionized water, and dried at 85℃ for 14 h to obtain cationic modified sepiolite. (3) The cationic modified sepiolite was dispersed in Tris-HCl buffer and ultrasonically dispersed for 60 min at an ultrasonic frequency of 40 kHz and a power of 500 W. Dopamine hydrochloride and ammonium persulfate were added and polymerized at 300 r / min for 8 h under light-protected conditions at 30 °C. (4) After the reaction was completed, the solid was collected by centrifugation at 5000 r / min for 15 min. The solid was dispersed in deionized water at a solid-liquid mass ratio of 1:10. Sodium sulfite was added and the pH was adjusted to 5.5 with 0.05 mol / L dilute hydrochloric acid. The mixture was stirred at 300 r / min for 30 min under nitrogen protection. The solid was then collected by centrifugation again and washed three times with deionized water. The solid was then dried at 65℃ and vacuum degree -0.09 MPa for 14 h to obtain polydopamine modified sepiolite fiber.
[0040] This embodiment also discloses a method for preparing a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware, comprising the following steps: S1. Slurry preparation: Bleached sulfate softwood pulp, bamboo pulp fiber, aramid pulp, mesoporous silica-supported lignin phosphate complex, and polydopamine-modified sepiolite fiber were added to a hydrapulper at a speed of 500 r / min. After pulping, the pulp was transferred to a desizing machine, and deionized water was added until the total mass fraction of the pulp was 6.0%. Cationic polyacrylamide was added, and the pulp was desizing at 50°C for 40 min to obtain primary pulp. S2, Functional slurry mixing: Add 2 / 3 of the total mass of the acrylate copolymer emulsion, 4 / 5 of the total mass of the hydrophobic fumed silica, the blocked waterborne isocyanate crosslinking agent, isothiazolinone, and hydroxypropyl methylcellulose ether to a mixing container and premix at 500 r / min for 15 min. Then add it to the primary slurry obtained in step S1 and stir at 500 r / min for 20 min. Adjust the pH of the slurry to 7.5 with 0.1 mol / L dilute ammonia or dilute hydrochloric acid to obtain the functional composite slurry. S3. Paper web forming and dewatering: After diluting the functional composite pulp to a head concentration of 1.2%, it is fed to the wire section of the fourdrinier paper machine. After vacuum filtration at a vacuum degree of -0.05MPa and three-stage press dewatering, a wet paper web with a dryness of 22% is obtained. The dewatering pressures of the three presses are 0.3 MPa, 0.4 MPa, and 0.5 MPa, respectively, and the paper web running speed is 12 m / min. S4. Drying and Surface Treatment: The wet paper web is subjected to gradient drying to a moisture content of 8%, followed by the application of a reinforced moisture-proof coating on its surface using a roller coating method. The coating material is composed of a uniform mixture of the remaining acrylic copolymer emulsion and the remaining hydrophobic fumed silica, with a coating weight of 15 g / m². 2 The solid content of the coating is 20%. The gradient drying process is as follows: Zone 1, 95℃, drying for 40 seconds; Zone 2, 110℃, drying for 45 seconds; Zone 3, 125℃, drying for 35 seconds; the paper web running speed during the drying process is 15 m / min. S5. Pressing and Corrugating: The paper web obtained in step S4 is passed through a single-face corrugator and manufactured into AB type corrugated board (A flute height 5.0 mm, number of flutes 38 / 300 mm; B flute height 3.0 mm, number of flutes 52 / 300 mm) under the conditions of temperature 165℃, pressure 0.5 MPa and board speed 90 m / min. S6. Die-cutting and gluing: Based on the size and shape of the shower fixtures, the corrugated cardboard is sequentially die-cut, printed, and grooved, and then bonded into boxes using polyurethane adhesive.
[0041] Example 3 discloses a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware. By weight, the raw materials for its preparation include: 55 parts of bleached sulfate softwood pulp with a beating degree of 35°SR, 18 parts of bamboo pulp fiber with a beating degree of 24°SR, 22 parts of acrylic copolymer emulsion with a solid content of 45%, 4 parts of hydrophobic fumed silica, 6 parts of aramid pulp, 4 parts of mesoporous silica-supported lignin phosphate composite, 10 parts of hydroxypropyl methylcellulose ether, 2.5 parts of polydopamine-modified sepiolite fiber, 3 parts of blocked waterborne isocyanate crosslinking agent, 0.8 parts of zinc pyrithione, and 0.35 parts of cationic polyacrylamide.
[0042] The raw materials for preparing the mesoporous silica-supported lignin phosphate complex, by weight, include: 100 parts alkali lignin, 22 parts phosphorus pentoxide, 3.5 parts hexadecyltrimethylammonium bromide, 25 parts tetraethyl orthosilicate, 7.5 parts ammonia, 400 parts N,N-dimethylformamide, 190 parts anhydrous ethanol, and 400 parts deionized water.
[0043] The preparation method of mesoporous silica-supported lignin phosphate complex includes the following steps: 1) In a dry reaction vessel, add alkali lignin and 5 / 6 of the total mass of N,N-dimethylformamide, and stir at 300 r / min for 45 min to dissolve; 2) Dissolve phosphorus pentoxide in the remaining N,N-dimethylformamide at 44℃; heat the system obtained in step 1) to 78℃, purge with nitrogen at a rate of 0.35 L / min for protection throughout the process, and add the mixture of phosphorus pentoxide and N,N-dimethylformamide dropwise at a rate of 7 mL / min while stirring continuously at 300 r / min. After the addition is complete, continue stirring and react for 4 h. 3) After the reaction is complete, pour the reaction solution obtained in step 2) into ice water at 3°C. The volume of ice water is 4 times the volume of the reaction solution. Let it stand for 45 minutes to settle, and then perform vacuum filtration. The filter paper pore size is 0.75μm and the filtration pressure is -0.07MPa. 4) The solid obtained by vacuum filtration was washed 4 times with deionized water. The mass of deionized water used each time was 12 times the mass of the solid. The washing was continued until the pH of the filtrate was 7.0. Then the washed solid was placed in a vacuum drying oven at 70℃ and a vacuum degree of -0.085MPa and dried for 13 hours to obtain phosphate ester grafted modified lignin. 5) Phosphate-grafted modified lignin and hexadecyltrimethylammonium bromide were dispersed in a mixed solvent of all deionized water and anhydrous ethanol and ultrasonically dispersed for 45 min at an ultrasonic frequency of 30 kHz and a power of 400 W. Then, the pH of the system was adjusted to 12.0 with 26% ammonia water, the temperature was raised to 52 °C, and pre-assembled at a stirring speed of 400 r / min for 2.5 h. 6) Add tetraethyl orthosilicate in three equal volumes to the system obtained in step 5), with an interval of 2.5 h between each batch, at a dropping rate of 12 mL / min. After the addition is complete, perform hydrothermal treatment at 82 °C for 14 h. After the reaction is complete, centrifuge at 4000 r / min for 13 min and collect the solid product. Wash the solid product with deionized water and anhydrous ethanol four times each, with each washing liquid volume being 9 times the mass of the solid. After Soxhlet extraction with anhydrous ethanol for 14 h to remove residual hexadecyltrimethylammonium bromide, dry at 60 °C and vacuum degree -0.085 MPa for 13 h to obtain the mesoporous silica-supported lignin phosphate complex.
[0044] The raw materials for preparing polydopamine-modified sepiolite fiber, by weight, include: 20 parts sepiolite fiber, 4.5 parts dopamine hydrochloride, 7 parts 3-aminopropyltriethoxysilane, 0.75 parts ammonium persulfate, 200 parts Tris-HCl buffer solution with a concentration of 0.015 mol / L, 0.2 parts sodium sulfite, and 250 parts deionized water.
[0045] The preparation method of polydopamine-modified sepiolite fiber includes the following steps: (1) Disperse sepiolite fibers in all deionized water, stir at 400 r / min for 45 min, adjust the pH of the system to 9.2 with 26% ammonia water, add 3-aminopropyltriethoxysilane, heat to 62℃, and stir at 400 r / min for 5 h. (2) After the reaction was completed, the pH of the system obtained in step (1) was neutralized to 6.7 with 0.15 mol / L dilute hydrochloric acid, filtered and washed 4 times with deionized water, and dried at 80℃ for 12 h to obtain cationic modified sepiolite. (3) The cationic modified sepiolite was dispersed in Tris-HCl buffer and ultrasonically dispersed for 45 min at an ultrasonic frequency of 30 kHz and a power of 400 W. Dopamine hydrochloride and ammonium persulfate were added and polymerized at 250 r / min for 7 h under the dark at 27 °C. (4) After the reaction was completed, the solid was collected by centrifugation at 4000 r / min for 12 min. The solid was dispersed in deionized water at a solid-liquid mass ratio of 1:9. Sodium sulfite was added, and the pH was adjusted to 5.0 with 0.05 mol / L dilute hydrochloric acid. The mixture was stirred at 250 r / min for 25 min under nitrogen protection. Then, the solid was collected by centrifugation again and washed three times with deionized water. The solid was then dried at 60℃ and vacuum degree -0.085 MPa for 12 h to obtain polydopamine modified sepiolite fiber.
[0046] This embodiment also discloses a method for preparing a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware, comprising the following steps: S1. Slurry preparation: Bleached sulfate softwood pulp, bamboo pulp fiber, aramid pulp, mesoporous silica-supported lignin phosphate complex, and polydopamine-modified sepiolite fiber were added to a hydrapulper at a speed of 400 r / min. After pulping, the pulp was transferred to a desizing machine, and deionized water was added until the total mass fraction of the pulp was 5%. Cationic polyacrylamide was added, and the pulp was desizing at 45°C for 35 min to obtain primary pulp. S2, Functional slurry mixing: Add 2 / 3 of the total mass of the acrylate copolymer emulsion, 4 / 5 of the total mass of the hydrophobic fumed silica, the blocked waterborne isocyanate crosslinking agent, zinc pyridine thione, and hydroxypropyl methylcellulose ether to a mixing container and premix at 400 r / min for 12 min. Then add it to the primary slurry obtained in step S1 and stir at 400 r / min for 16 min. Adjust the pH of the slurry to 7.0 with 0.07 mol / L dilute ammonia or dilute hydrochloric acid to obtain the functional composite slurry. S3. Paper web forming and dewatering: After diluting the functional composite pulp to a head concentration of 1.0%, it is fed to the wire section of the fourdrinier paper machine. After vacuum filtration at a vacuum degree of -0.04MPa and three-stage press dewatering, a wet paper web with a dryness of 20% is obtained. The dewatering pressures of the three presses are 0.25 MPa, 0.35 MPa, and 0.45 MPa, respectively, and the paper web running speed is 10 m / min. S4. Drying and Surface Treatment: The wet paper web is subjected to gradient drying to a moisture content of 7%, followed by the application of a reinforced moisture-proof coating on its surface using a roller coating method. The coating material is composed of a uniform mixture of the remaining acrylic copolymer emulsion and the remaining hydrophobic fumed silica, with a coating weight of 11 g / m². 2 The solid content of the coating is 17%. The gradient drying process is as follows: Zone 1, 88℃, drying for 35 seconds; Zone 2, 105℃, drying for 40 seconds; Zone 3, 120℃, drying for 30 seconds; the paper web running speed during the drying process is 12 m / min. S5. Pressing and Corrugating: The paper web obtained in step S4 is passed through a single-face corrugator and made into AB type corrugated board (A flute height 4.7mm, number of flutes 36 / 300mm; B flute height 2.7mm, number of flutes 50 / 300mm) under the conditions of temperature 158℃, pressure 0.4MPa and board speed 75m / min. S6. Die-cutting and gluing: Based on the size and shape of the shower fixtures, the corrugated cardboard is sequentially die-cut, printed, and grooved, and then bonded into boxes using polyurethane adhesive.
[0047] Comparative Example 1: A pressure-resistant and moisture-proof packaging carton for shower and sanitary ware and its preparation method are disclosed. The only difference between this carton and Example 3 is that no mesoporous silica-supported lignin phosphate complex is added.
[0048] Comparative Example 2: A pressure-resistant and moisture-proof packaging carton for shower and sanitary ware and its preparation method are disclosed. The only difference between this carton and Example 3 is that polydopamine-modified sepiolite fiber is not added.
[0049] Comparative Example 3: A pressure-resistant and moisture-proof packaging carton for shower and sanitary ware and its preparation method are disclosed. The only difference between this carton and Example 3 is that no aramid pulp is added.
[0050] Comparative Example 4: A pressure-resistant and moisture-proof packaging carton for shower and sanitary ware and its preparation method are disclosed. The only difference between this carton and Example 3 is that the acrylic copolymer emulsion is replaced with an equal amount of ordinary styrene-acrylic emulsion (45% solid content, purchased from Hubei Xinrunde Chemical Co., Ltd.).
[0051] Comparative Example 5: A pressure-resistant and moisture-proof packaging carton for shower and sanitary ware and its preparation method are disclosed. The only difference between this carton and Example 3 is that hydrophobic fumed silica is not added.
[0052] Comparative Example 6: A pressure-resistant and moisture-proof packaging carton for shower and sanitary ware and its preparation method are disclosed. The only difference between the carton and Example 3 is that bamboo pulp fiber is replaced with an equal amount of ordinary softwood pulp fiber (beating degree 24°SR, wet weight 7g, specifications 1.67dtex×38mm, purchased from Nanjing Lenzing Fibers Co., Ltd.).
[0053] Comparative Example 7: A pressure-resistant and moisture-proof packaging carton for shower sanitary ware and its preparation method are different from those in Example 3 only in that: when preparing polydopamine-modified sepiolite fiber, the polydopamine hybridization step is omitted and cationic modified sepiolite is used directly (i.e., no dopamine hydrochloride, ammonium persulfate, Tris-HCl buffer, sodium sulfite are added, and steps (3) and (4) are not performed).
[0054] Comparative Example 8: Use commercially available ordinary corrugated cardboard boxes.
[0055] The edge crush strength, bursting strength, adhesive strength, static contact angle, water absorption, strength retention rate after damp heat cycling, empty box compressive strength, mildew resistance rating, and nano-SiO2 retention rate of the packaging cartons obtained in Examples 1-3 and Comparative Examples 1-8 were tested. The testing methods and standards for each performance are as follows: 1. Edge crush strength test: The test was conducted in accordance with the national standard GB / T 6546-1998 Determination of edge crush strength of corrugated cardboard. A compression testing machine was used, with a sample size of 25mm×100mm and a loading speed of 12.5mm / min. The average value of 10 samples was taken.
[0056] 2. Bursting strength test: The test shall be conducted in accordance with the national standard GB / T 6545-1998 Determination of bursting strength of corrugated cardboard. A bursting strength tester shall be used, the sample diameter shall not be less than 70 mm, and the pressure shall be increased at a flow rate of 170 mL / min during the test. The average value of 12 samples shall be taken.
[0057] 3. Adhesion strength test: The test shall be conducted in accordance with the national standard GB / T 6548-2011 Determination of adhesive strength of corrugated cardboard, using the peel test method, with a sample size of 25mm×150mm, a loading speed of 60-80mm / min, and the average value of 10 samples shall be taken.
[0058] 4. Static contact angle test: Using a contact angle meter, take 5 μL of deionized water and drop it onto a flat area of the sample surface. Measure the contact angle after 30 seconds. Measure 5 different positions for each sample and take the average value.
[0059] 5. Water absorption test: The test shall be conducted in accordance with the national standard GB / T 1540-2002 Determination of water absorption of paper and paperboard (Cobb method) for 60 seconds, and the average value of 5 samples shall be taken.
[0060] 6. Strength retention rate test after damp heat cycling: Place the sample in a constant temperature and humidity chamber and treat it at 40℃ and 90% relative humidity for 48 hours, followed by drying in a 50℃ oven for 12 hours. This constitutes one cycle. After 5 cycles, determine the edge crush strength according to GB / T 6546. The strength retention rate is calculated using the formula: Retention rate = Edge crush strength after 5 cycles / Initial edge crush strength × 100%.
[0061] 7. Empty box compression strength test: The test was conducted in accordance with the national standard GB / T 4857.4-2008 Packaging and Transport Packaging - Basic Tests - Part 4: Compression and Stacking Tests Using a Compression Testing Machine. A standard AB corrugated cardboard box of type 0201 with dimensions of 400mm×300mm×300mm was prepared, with a loading speed of 10mm / min. The average value of 5 boxes was taken.
[0062] 8. Anti-mold level test: Conducted according to the national standard GB / T 4768-2008 Anti-mold Packaging, inoculated with a mixed spore suspension of Aspergillus niger, Penicillium, and Rhizopus, at a concentration of 10. 6 -10 7 The sample was cultured at 28℃ and ≥90% relative humidity for 28 days, and the anti-mold level was evaluated according to Table 1 in the standard.
[0063] 9. Detection of nano-SiO2 retention rate: The ashing method was used for determination. After the pulp was made into sheets and dried, 10g of paper sample was taken and burned in a muffle furnace at 575℃ for 3 hours. The SiO2 content in the ash was determined. The retention rate was calculated as follows: Retention rate = mass of SiO2 in paper sample / mass of added SiO2 × 100%.
[0064] The results are shown in Tables 2 and 3.
[0065] Table 2 Test results of physical properties and moisture resistance of corrugated cardboard
[0066] Table 3. Results of performance and durability tests on finished empty boxes
[0067] Using Example 3 as the control group, the performance differences and causes of Comparative Examples 1-8 are analyzed as follows: Comparative Example 1: Without the addition of the mesoporous silica-supported lignin phosphate composite, the edge crush strength decreased from 8650 N / m to 7750 N / m (a decrease of 10.4%), and the retention rate during wet-heat cycling decreased from 86.0% to 76.0% (a decrease of 11.6%). The mesoporous silica-supported lignin phosphate composite can fill the gaps between fibers, optimize the interfiber interface bonding state, and improve the structural stability of the fiber network under high humidity conditions. Its ordered mesoporous shell can act as a slow-release carrier for lignin phosphate, promoting its enrichment at the fiber interface and achieving dynamic reinforcement and moisture protection under high humidity conditions. Without this component, there is no dynamic reinforcing material at the fiber interface under high humidity conditions, and the attenuation of the interfiber bonding force cannot be compensated, thus resulting in a significant decrease in the retention rate during wet-heat cycling. At the same time, due to the lack of the basic filling and reinforcing effect of this component on the fiber network, the initial edge crush strength decreased slightly.
[0068] Comparative Example 2: Without the addition of polydopamine-modified sepiolite fiber, the edge compressive strength decreased from 8650 N / m to 7150 N / m (a decrease of 17.3%), the burst strength decreased from 1850 kPa to 1550 kPa (a decrease of 16.2%), the bond strength decreased from 720 N / m to 500 N / m (a decrease of 30.6%), and the empty box compressive strength decreased from 7100 N to 4250 N (a decrease of 40.1%). The cationic modified segment of polydopamine-modified sepiolite fiber can form electrostatic adsorption with negatively charged cellulose and aramid pulp. The surface polydopamine layer can achieve strong bonding with various reinforcing components and matrix fibers through covalent bonds, hydrogen bonds, and π-π stacking, which is the key to ensuring efficient stress transfer. Without this component, the interfacial bonding force between the fiber network and the reinforcing components is significantly weakened, and stress cannot be effectively dispersed, resulting in a significant decrease in various structural strength indicators and empty box compressive strength.
[0069] Comparative Example 3: Without the addition of aramid pulp, the bursting strength decreased from 1850 kPa to 1450 kPa (a decrease of 21.6%), the empty box compressive strength decreased from 7100 N to 4400 N (a decrease of 38.0%), and the edge crush strength decreased from 8650 N / m to 7250 N / m (a decrease of 16.2%). Aramid pulp is a highly crystalline, high-modulus reinforcing component that can be embedded in the fiber network to achieve efficient absorption and dispersion of external pressure and bursting stress, making it key to improving the bursting strength and empty box compressive strength of cartons. The absence of this component significantly reduces the fiber network's resistance to bursting and compression, resulting in a significant decrease in bursting strength and empty box compressive strength. In contrast, bamboo pulp fiber and mesoporous silica-supported lignin phosphate composites can still provide basic reinforcement, thus the decrease in edge crush strength is relatively smaller.
[0070] Comparative Example 4: Replacing the acrylate copolymer emulsion with ordinary styrene-acrylic emulsion reduced the static contact angle from 125° to 102° (a decrease of 18.4%), and the Cobb value from 28 g / m³. 2 Increased to 42g / m 2 (Increase of 50%), the wet heat cycle retention rate decreased from 86.0% to 70.8% (a decrease of 17.7%), and the empty box compressive strength decreased from 7100N to 4350N (a decrease of 38.7%). Acrylic copolymer emulsion is the core film-forming hydrophobic component, which can form a continuous and dense hydrophobic film layer on the fiber surface, synergistically enhancing the overall hydrophobic performance with hydrophobic fumed silica. Ordinary styrene-acrylic emulsion has a low content of hydrophobic functional groups, resulting in a poorly dense film layer. It cannot form an effective synergistic hydrophobic system with hydrophobic fumed silica, and the fiber surface lacks effective hydrophobic protection. Therefore, the static contact angle decreases and water absorption increases significantly. Under high humidity conditions, fibers without hydrophobic film protection swell significantly, and the inter-fiber bonding force rapidly decays, leading to a significant decrease in wet heat cycle retention rate and empty box compressive strength.
[0071] Comparative Example 5: Without the addition of hydrophobic fumed silica, the Cobb value decreased from 28 g / m³. 2 Increased to 50g / m 2 (Increase of 78.5%), the retention rate of nano-SiO2 was 0, and the static contact angle decreased from 125° to 95° (decrease of 24.0%). Hydrophobic fumed silica modified with trimethylchlorosilane achieved a surface hydroxyl coverage of ≥85%, forming a synergistic hydrophobic structure with the hydrophobic film layer of acrylate copolymer emulsions. Simultaneously, it filled the micropores between fibers, improving the density of the hydrophobic film layer. Furthermore, this modified silica synergistically improved the retention rate of nanofillers with cationic polyacrylamide retention aids. Without this component, the micropores between fibers were not filled, resulting in a decrease in the density of the hydrophobic film layer, thus significantly increasing water absorption and reducing the static contact angle.
[0072] Comparative Example 6: When bamboo pulp fiber was replaced with softwood pulp fiber, the edge compressive strength decreased from 8650 N / m to 8100 N / m (a decrease of 6.4%), the bursting strength decreased from 1850 kPa to 1620 kPa (a decrease of 12.4%), the empty box compressive strength decreased from 7100 N to 4700 N (a decrease of 33.8%), and the wet heat cycle retention rate increased from 86.0% to 83.0% (a decrease of 3.5%). Bamboo pulp fiber (1.67 dtex × 38 mm) has a better aspect ratio than ordinary softwood pulp fiber, which can improve the fiber network interweaving and toughness. The density of the fiber network decreased slightly after replacement, resulting in a slight decrease in edge crush, bursting strength and empty box compression strength. This indicates that the bamboo pulp fiber's effect on improving fiber interlacing is more beneficial to the overall protective performance of the carton. Meanwhile, the hydrophilicity of softwood pulp fiber is slightly lower than that of bamboo pulp fiber, resulting in less swelling under high humidity conditions and higher fiber network structure stability. Therefore, the retention rate during wet and heat cycling is slightly improved.
[0073] Comparative Example 7: When preparing polydopamine-modified sepiolite fibers, the polydopamine hybridization step was omitted, and cationic modified sepiolite was used directly. The bond strength decreased from 720 N / m to 610 N / m (a decrease of 15.3%), the empty box compressive strength decreased from 7100 N to 4300 N (a decrease of 39.4%), and the edge crush strength decreased from 8650 N / m to 7400 N / m (a decrease of 14.4%). The polydopamine layer can form multiple bonding effects with cellulose fibers, aramid pulp, and mesoporous silica-supported lignin phosphate complexes through covalent bonds, hydrogen bonds, and π-π stacking. Pure cationic modified sepiolite can only bind to fibers through electrostatic adsorption, and the interfacial forces are weaker than the multiple bonding effects after polydopamine modification. Omitting polydopamine hybridization significantly reduces the interfacial bonding force between components, resulting in a substantial decrease in adhesive strength and interfacial bonding energy. The attenuation of interfacial adhesion leads to a decrease in stress transfer efficiency, which in turn significantly reduces the compressive strength of the empty box. The cationic modification segment can still play a basic electrostatic adsorption role, so the decrease in edge pressure strength is relatively small.
[0074] Comparative Example 8: Using commercially available ordinary corrugated cardboard boxes, the mildew resistance level dropped to level 3. Commercially available ordinary corrugated cardboard boxes lack dedicated reinforcing, hydrophobic, mildew-resistant, and interface-modifying components. The basic strength of the ordinary corrugated paper fiber network is low, and the starch adhesive, being a hydrophilic binder, is prone to softening and failure in high humidity environments, leading to a sharp decline in the bonding force between fibers and a significant decrease in various structural strength indicators. The lack of hydrophobic components leaves the fiber surface without any hydrophobic protection, resulting in a dramatic increase in water absorption and a significant decrease in the static contact angle. The absence of mildew inhibitors fails to suppress mold growth, thus deteriorating the mildew resistance level. The lack of nano-hydrophobic fillers results in a 0% retention rate of nano-SiO2.
[0075] In summary, the acrylic copolymer emulsion forms a dense film on the fiber surface, synergistically enhancing the overall moisture-proof performance of the carton with hydrophobic fumed silica. Aramid pulp strengthens the carton's resistance to breakage and compression, while the mesoporous silica-loaded lignin phosphate composite optimizes interfacial bonding between fibers, improving the carton's environmental adaptability and structural stability. Hydroxypropyl methylcellulose ether provides initial adhesion between components and helps seal fiber pores. Polydopamine-modified sepiolite fibers significantly improve interfacial compatibility among components, promoting efficient stress transfer within the substrate. The synergistic and complementary effects of these components endow the packaging carton with excellent structural strength, moisture resistance, mildew resistance, compression resistance, and breakage resistance, effectively extending its service life and meeting the protective requirements for the storage and transportation of shower and sanitary ware.
[0076] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A pressure-resistant and moisture-proof packaging carton for shower and bathroom fixtures, characterized in that, The raw materials for its preparation, by weight, include: 40-70 parts of bleached sulfate softwood pulp, 10-25 parts of bamboo pulp fiber, 15-30 parts of acrylate copolymer emulsion, 2-6 parts of hydrophobic fumed silica, 3-10 parts of aramid pulp, 2-6 parts of mesoporous silica-supported lignin phosphate complex, 5-15 parts of hydroxypropyl methylcellulose ether, 1-4 parts of polydopamine-modified sepiolite fiber, 2-4 parts of blocked waterborne isocyanate crosslinking agent, 0.5-1.1 parts of mildew inhibitor, and 0.2-0.5 parts of cationic polyacrylamide.
2. The pressure-resistant and moisture-proof packaging carton for shower and sanitary ware according to claim 1, characterized in that, The bleached sulfate softwood pulp has a freeness of 32-38°SR, and the bamboo pulp fiber has a freeness of 20-28°SR; the acrylate copolymer emulsion has a solid content of 40%-45%; the mildew inhibitor is zinc pyrithione or isothiazolinone.
3. The pressure-resistant and moisture-proof packaging carton for shower and sanitary ware according to claim 1, characterized in that, The raw materials for preparing the mesoporous silica-supported lignin phosphate composite, by weight, include: 80-120 parts of alkali lignin, 15-30 parts of phosphorus pentoxide, 2-5 parts of hexadecyltrimethylammonium bromide, 20-30 parts of tetraethyl orthosilicate, 5-10 parts of ammonia, 350-450 parts of N,N-dimethylformamide, 150-230 parts of anhydrous ethanol, and 300-500 parts of deionized water.
4. The pressure-resistant and moisture-proof packaging carton for shower and sanitary ware according to claim 3, characterized in that, The preparation method of the mesoporous silica-supported lignin phosphate complex includes the following steps: 1) In a dry reaction vessel, add 2 / 3-5 / 6 of the total mass of alkali lignin and N,N-dimethylformamide, and stir at 200-400 r / min to dissolve for 30-60 min; 2) Dissolve phosphorus pentoxide in the remaining N,N-dimethylformamide at 42-46℃; heat the system obtained in step 1) to 70-85℃, purge with nitrogen at a rate of 0.2-0.5 L / min for protection throughout the process, and add the mixture of phosphorus pentoxide and N,N-dimethylformamide dropwise at a rate of 5-10 mL / min while stirring continuously at 200-400 r / min. After the addition is complete, continue stirring and react for 3-5 h. 3) After the reaction is complete, pour the reaction solution obtained in step 2) into ice water at 0-5℃. The volume of ice water is 3-5 times the volume of the reaction solution. Let it stand for 30-60 minutes to settle, and then perform vacuum filtration. The filter paper pore size is 0.45-1.0μm, and the filtration pressure is -0.06MPa to -0.08MPa. 4) The solid obtained by vacuum filtration is washed with deionized water 3-5 times until the pH of the filtrate is 6.5-7.
5. Then the washed solid is placed in a vacuum drying oven at 60-80℃ and a vacuum degree of -0.08MPa to -0.09MPa for 10-16 hours to obtain phosphate ester grafted modified lignin. 5) Disperse phosphate-grafted lignin and hexadecyltrimethylammonium bromide in a mixed solvent of all deionized water and anhydrous ethanol, and ultrasonically disperse for 30-60 min at an ultrasonic frequency of 20-40 kHz and a power of 300-500 W; then adjust the pH of the system to 11.5-12.0 with ammonia water with a mass fraction of 25%-28%, raise the temperature to 50-55℃, and pre-assemble at a stirring speed of 300-500 r / min for 2-3 h. 6) Add tetraethyl orthosilicate in three equal volumes to the system obtained in step 5), with an interval of 2-3 hours between each batch, at a dropping rate of 10-15 mL / min. After the addition is complete, perform hydrothermal treatment at 80-85℃ for 12-16 hours. After the reaction is complete, centrifuge at 3000-5000 r / min for 10-15 minutes, collect the solid product, wash the solid product with deionized water and anhydrous ethanol 3-4 times each, extract with anhydrous ethanol using Soxhlet extraction for 12-16 hours to remove residual hexadecyltrimethylammonium bromide, and then dry at 55-65℃ and a vacuum of -0.08 MPa to -0.09 MPa for 10-16 hours to obtain the mesoporous silica-supported lignin phosphate complex.
5. The pressure-resistant and moisture-proof packaging carton for shower and sanitary ware according to claim 1, characterized in that, The raw materials for preparing the polydopamine-modified sepiolite fiber, by weight, include: 15-25 parts sepiolite fiber, 3-6 parts dopamine hydrochloride, 5-10 parts 3-aminopropyltriethoxysilane, 0.5-1.0 parts ammonium persulfate, 150-250 parts Tris-HCl buffer solution with a concentration of 0.01-0.02 mol / L, 0.1-0.3 parts sodium sulfite, and 200-300 parts deionized water.
6. The pressure-resistant and moisture-proof packaging carton for shower and sanitary ware according to claim 5, characterized in that, The preparation method of the polydopamine-modified sepiolite fiber includes the following steps: (1) Disperse sepiolite fibers in all deionized water, stir at 300-500 r / min for 30-60 min, adjust the pH of the system to 9.0-9.5 with ammonia water with a mass fraction of 25%-28%, add 3-aminopropyltriethoxysilane, heat to 60-65℃, and stir at 300-500 r / min for 4-6 h. (2) After the reaction is complete, the pH of the system obtained in step (1) is neutralized to 6.5-7.0 with 0.1-0.2 mol / L dilute hydrochloric acid. After filtration, it is washed 3-4 times with deionized water and dried at 75-85℃ for 10-14h to obtain cationic modified sepiolite. (3) Disperse the cationic modified sepiolite in Tris-HCl buffer, and ultrasonically disperse it for 30-60 min under ultrasonic frequency of 20-40 kHz and power of 300-500 W. Add dopamine hydrochloride and ammonium persulfate, and polymerize it at 200-300 r / min for 6-8 h under light-protected conditions at 25-30 ℃. (4) After the reaction is complete, centrifuge at 3000-5000 r / min for 10-15 min, collect the solid, disperse the obtained solid in deionized water at a solid-liquid mass ratio of 1:8-10, add sodium sulfite, adjust the pH to 4.5-5.5 with 0.05 mol / L dilute hydrochloric acid, and stir at 200-300 r / min for 20-30 min under nitrogen protection; The solid was then centrifuged again, collected, and washed 2-3 times with deionized water. It was then dried at 55-65℃ and a vacuum of -0.08MPa to -0.09MPa for 10-14 hours to obtain polydopamine-modified sepiolite fiber.
7. A method for preparing a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Slurry preparation: Bleached sulfate softwood pulp, bamboo pulp fiber, aramid pulp, mesoporous silica-supported lignin phosphate complex, and polydopamine-modified sepiolite fiber are added to a hydrapulper for pulping, then transferred to a desizing machine. Deionized water is added until the total mass fraction of the pulp is 4.0%-6.0%. Cationic polyacrylamide is added, and the pulp is desizing at 40-50℃ for 30-40 minutes to obtain primary pulp. S2, Functional slurry mixing: Add 1 / 2 to 2 / 3 of the total mass of the acrylate copolymer emulsion, 7 / 10 to 4 / 5 of the total mass of the hydrophobic fumed silica, the blocked waterborne isocyanate crosslinking agent, the mildew inhibitor, and the hydroxypropyl methylcellulose ether to a mixing container and premix evenly. Then add it to the primary slurry obtained in step S1 and stir at 300-500 r / min for 10-20 min. Adjust the pH of the slurry to 6.5-7.5 with 0.05-0.1 mol / L dilute ammonia or dilute hydrochloric acid to obtain the functional composite slurry. S3. Paper web forming and dewatering: The functional composite pulp is diluted to a head concentration of 0.8%-1.2% and then fed to the wire section of the fourdrinier paper machine. After vacuum filtration at a vacuum degree of -0.03MPa to -0.05MPa and three-stage press dewatering, a wet paper web is obtained. S4. Drying and Surface Treatment: The wet paper web is subjected to gradient drying to a moisture content of 6%-8%, followed by the application of a reinforced moisture-proof coating on its surface using a roller coating method. The coating material is composed of a uniform mixture of the remaining acrylic copolymer emulsion and the remaining hydrophobic fumed silica, with a coating weight of 8-15 g / m². 2 The solid content of the coating is 15%-20%; S5. Pressing and Corrugated Forming: The paper web obtained in step S4 is passed through a single-face corrugator and processed into AB type corrugated board under the conditions of temperature 150-165℃, pressure 0.3-0.5MPa, and board speed 60-90m / min. S6. Die-cutting and gluing: Based on the size and shape of the shower fixtures, the corrugated cardboard is sequentially die-cut, printed, and grooved, and then bonded into boxes using polyurethane adhesive.
8. The method for preparing a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware according to claim 7, characterized in that, In step S1, the speed of the hydraulic pulper is 300-500 r / min; in step S2, the stirring speed of the premix is 300-500 r / min, and the time is 10-15 min.
9. The method for preparing a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware according to claim 7, characterized in that, In step S3, the dewatering pressures of the three presses are 0.2-0.3 MPa, 0.3-0.4 MPa, and 0.4-0.5 MPa, respectively, and the paper web running speed is 8-12 m / min; the dryness of the wet paper web after pressing is 18%-22%.
10. The method for preparing a pressure-resistant and moisture-proof packaging carton for shower and sanitary ware according to claim 7, characterized in that, In step S4, the gradient drying process is as follows: Zone 1, 80-95℃, drying for 30-40s; Zone 2, 100-110℃, drying for 35-45s; Zone 3, 115-125℃, drying for 25-35s; the paper web running speed during the drying process is 10-15m / min.